Extension of Spread-Slump Formulae for Yield Stress Evaluation - Pierre Alexandre; Lanos Christophe; Estellé Patrice (Applied Rheology, 2013)
This paper provides a new model to evaluate the yield stress of suspensions, slurries or pastes, based on the release of a finite volume of material onto a horizontal surface. Considering the height (h) and the radius (R) of the sample at the flow stoppage, two asymptotic regimes, where h > R or h < R, lead to different analytical models that allow the determination of yield stress. Experimental observations show typical sample shape at stoppage between slump (h > R) and spread (h < R). Based on these observations, we have developed a new analytical model to evaluate accurately the yield stress of materials in this intermediate regime. The validity of this model was evaluated from data obtained using various CarbopolR dispersions. The yield stress measured with the proposed model was compared with the yield stress evaluated from shear flow curves obtained with roughened plate/plate geometry fitted to the Herschel-Bulkley model. Results show the relevance of the proposed model which that can be applied in the range between models used for the two asymptotic regimes.